Development of blast disease-resistant transgenic rice variety from MR219 through transformation with Pikh gene - Azizi, Parisa (2015)
Food security has become a concern of global importance, and major price spike of staple food crops, such as rice has occurred in recent years. These price spikes are partly due to the brunt of plant disease. Magnapor the oryzae, rice blast fungus, is a plant pathogen causes a serious rice disease and therefore poes a threat to the world‟s important food security crop. Planttrans formation technology has become an adaptable system for cultivar development and also for functional analysis of gene in plants. The objectives of this study were (i) to screen Malaysian rice varieties phenotypically, physiologically and genetically against blast disease (ii) to isolate Pikh gene from leaves of resistant rice variety (PH9), (iii) to construct the over-expression vector carrying CDS of Pikhgene,and (iv) to determine the effects of (over-expression)of Pikh in MR219 rice variety. Sixteen important Malaysian rice varieties were screened phenotypically (by scoring), physiologically (measuring photosynthesis and its components) and genetically (gene expression analysis using Real-Time PCR). Specific primer was designed to isolate full Coding DNA Sequence (CDS) of Pikh gene from PH9 rice variety. Entry and the expression vectors were constructed using the Gateway Technology. Agrobacterium-mediated transformation technology was used to introduce Pikh gene to the callus of MR219. Transgenic plants were evaluated from DNA to protein stages by polymerase chain reaction (PCR),Semi-quantitative RT-PCR, Real-Time PCR, high performance liquid chromatography. Transgenic plants also were compared to the control plants using Real-Time quantification technique (to quantify pathogen population) and also challenging of transgenic and control plants with the local most virulent M. oryzaepathotype, P7.2. The TRIzol method was quick and reliable method for RNA extraction from leaves of rice. Ten out of 16 varieties (MR159, PH9,MR84, MR185, MR253, MR269, MRQ74, MRQ50, Pulut Siding and Pongsu Seribu 2) demonstrated high degree of resistance to pathotype P7.2 rice leaf blast. Photosynthesis and chlorophyll contents were decreased significantly among treated susceptible varieties compared to the controls. There were absent of differences in photosynthesis and its components between inoculated and noninoculated resistant varieties. Hence, it seems that energy sources are provided for both resistant and susceptible plants, but the expression of defence-associated genes restricts the pathogens accessibility in the resistant varieties.Our findings provide evidences that the expression profiling of Pikh, Pi9, Pi21, and Osw45 genes is involved in the defense responses in the leaves of rice 31 h after inoculation of plants by M. oryzae. Full CDS ofPikhgene with 1206 bp length was obtained through amplification of the cDNA template using specific primer. Pikh gene was up-regulated in the transgenic plants in comparison to the control plants. The amount of leucine amino acid of transgenic rice plants has increased significantly from 17.131 in the wild-type to 47.865 mg g-1. The M.oryzae population was constant at 31, 48 and 72h after inoculation in transgenic plants while itincreased in inoculated control plants. This study successfully clarified that over-expression of Pikh gene in the transgenic plants is able to improve the resistance of rice against M.oryzaepathotype P7.2.